Pengaruh Tingkat Kepercayaan Diri Dan Keterampilan Berkomunikasi Terhadap Kemampuan Public Speaking Mahasiswa Program Studi Pendidikan Ekonomi Angkatan 2020-2021 Universitas Jambi - Setiawati Tampubolon, Dyah; Suratno, Suratno; Arief, Hidayatul (Edu Sosial, 2023)
The aim of this research is to describe the influence of Self-Confidence and Communication Skills on the Public Speaking Ability of Students in the Class of 2020-2021 Economic Education at Jambi University. This research uses quantitative research with descriptive analysis methods. The population of this study consisted of 174 respondents who were students from the 2020-2021 class of Economic Education at Jambi University. The data collection method uses Google forms to distribute questionnaires. Multiple linear regression analysis with the help of the Ms tool. Excel and data analysis SPPS 22.0 for Windows. The research results show that there is an influence between the variables of self-confidence and communication skills on students' public speaking abilities. The calculated t value for the self-confidence variable (X1) was 6.179 and the t table was 1.657 or 6.179>1657. From the calculated t value for the communication skills variable (X2) it was 5.953 and the t table was 1.657 or 5.953>1.657. And the F test obtained an Fcount value of 28.135 and an Ftable of 3.07 or 28.135>3.07. So it can be stated that H03 is rejected and Ha3 is accepted, which means that there is an influence between self-confidence and communication skills on public speaking abilities. From this research it can be concluded that self-confidence and positive communication skills will influence students' public speaking abilities.